How effective are trading pauses? - Nikolaus Hautsch; Akos Horvath (Goethe University Frankfurt, Center for Financial Studies (CFS), 2017)
Exploiting NASDAQ order book data and difference-in-differences methodology, we identify the distinct effects of trading pause mechanisms introduced on U.S. stock exchanges after May 2010. We show that the mere existence of such a regulation constitutes a safeguard which makes market participants behave differently in anticipation of a pause. Pauses tend to break local price trends, make liquidity suppliers revise positions, and enhance price discovery. In contrast, pauses do not have a "cool off" effect on markets, but rather accelerate volatility and bid-ask spreads. This implies a regulatory trade-off between the protective role of trading pauses and their adverse effects on market quality.
urn:nbn:de:hebis:30:3-431613
Keywords: G10; G14; G18; 330; trading pause; "magnet effect"; price discovery; volatility; liquidity